Next‐Generation Energy Harvesting and Storage Technologies for Robots Across All Scales. (12th June 2022) - Liang, Zexi; He, Jiarui; Hu, Chuangang; Pu, Xiong; Khani, Hadi; Dai, Liming; Fan, Donglei (Emma); Manthiram, Arumugam; Wang, Zhong-Lin
Abstract : Self‐powered untethered robots that can meander unrestrictedly, squeeze into small spaces, and operate in diverse harsh environments have received immense attention in recent years. As there is not a universal solution that can be applied to power robots with diverse forms, service functions, and a broad size range from nanometers to meters, the design, fabrication, and implementation of power systems with a suitable weight, desired power and operation duration, and adaptiveness to confined spaces and operation conditions represent one of the greatest challenges in robotic research. Herein, an overview of recent progress and challenges in developing the next‐generation energy harvesting and storage technologies is provided, including direct energy harvesting, energy storage and conversion, and wireless energy transmission for robots across all scales. Abstract : Self‐powered untethered robots with sizes ranging from the molecular scale to meters have received immense attention. However, due to the diverse forms, service functions, and broad size range, there is no universal solution for powering all robots. This work overviews the recent progress and challenges in developing the next‐generation energy harvesting and storage technologies for robots across all scales.